Desain Pembelajaran PAI Kontekstual Multikultural Di Madrasah Ibtidaiyah Berbasis ICT - Rofiah, Siti (AL-WIJDÃN Journal of Islamic Education Studies, 2016)
Multicultural education as a sub education has a strategic role in the formation of personal children as early as possible. Multicultural education in Islam in general can be understood as an effort to increase faith, understanding, appreciation and practice of children about Islam so that it becomes a pious Muslim personal and uphold morality in personal life, society, nation and state. The context of the society, nation and state indirectly require an educational format that the form-implementable method that is ready practiced in the school / madrasah. In this respect the development-based research needed to find a format that is ideal in the implementation of the concept of multicultural education in general. The method used in this research is the development (Research Development) 4-D model namely, the definition, the design, Development, and Dissemination. Becomes interesting when it is able to find a development study format multicultural education for children, so that education becomes optimal touch. Optimaly education in the perspective of Islamic education is touching the two main elements of education are elements of the world and the akhirat elements. Urgency in finding implementable concepts that will require an accurate and in depth analysis. A multicultural perspective into urgent bid as an educational concept that can be implemented into guidelines and methods of education of children in the present era. The results of this study may indicate that PPKM models can stimulate and improve students' understanding of concepts as well as to foster a love of students towards subjects PAI. Learning implementation went smoothly, the response of students and teachers was also good. Keywords: Multicultural education, the concept of education, children's education